SERUM SALUSIN-? LEVEL IN BEHCET'S DISEASE - Ozgen, Metin; Koca, Suleyman Serdar; Dagli, Necati; Yavuzkir, Mustafa; Ustundag, Bilal; Isik, Ahmet (Clinical & Exper Rheumatology, 2010)
[Abstract Not Available]